1998
DOI: 10.1111/j.1469-7793.1998.793bj.x
|View full text |Cite
|
Sign up to set email alerts
|

NMDA and GABAAreceptors in the rat Kölliker‐Fuse area control cardiorespiratory responses evoked by trigeminal ethmoidal nerve stimulation

Abstract: 1. Electrical stimulation (10 s) of the ethmoidal nerve (EN5) evokes the nasotrigeminal reflex responses, including apnoea, bradycardia and rise in arterial blood pressure. In the present study, we examined the involvement of N-methyl-ª_aspartate (NMDA), AMPAÏkainate, (ã_aminobutyric acidA (GABAA) and glycine receptors in the K olliker-Fuse (KF) nucleus in the mediation of the nasotrigeminal reflex responses. 2. Unilateral injections (n = 6) of 50-100 nl of the NMDA receptor antagonist AP5 into the KF area led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 37 publications
3
64
0
Order By: Relevance
“…A total of 20 studies were identified that reported a relationship between KF and cranial nerve function, and these involved the trigeminal (6 studies) [14][15][16][17][18][19], vagus (9) [4,[20][21][22][23][24][25][26][27] and hypoglossal (5) [28][29][30][31][32] nerves. The experimental techniques used in obtaining these findings are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 studies were identified that reported a relationship between KF and cranial nerve function, and these involved the trigeminal (6 studies) [14][15][16][17][18][19], vagus (9) [4,[20][21][22][23][24][25][26][27] and hypoglossal (5) [28][29][30][31][32] nerves. The experimental techniques used in obtaining these findings are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated that the KF is a mandatory relay site for the mediation of trigeminally evoked apnea and bradycardia, which represent the hallmarks of the diving response Herbert, 1996, 1997). Injections of the GABA A receptor antagonist bicuculline into the KF prior to trigeminal ethmoidal nerve stimulation led to a strong enhancement of the reflex responses (Dutschmann and Herbert, 1998), suggesting that KF neurons are under a potent GABAergic inhibition. Lack of this GABAergic inhibition in the KF might be important with respect to life-threatening phenomena such as the sudden infant death syndrome.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…At the same time, it has been demonstrated that chemical or electrical stimulation of the medial parabrachial complex (mPB) or Kö lliker -Fuse nucleus (KF) can evoke phase resetting and IOS in vagi intact animals (Oku & Dick 1992;Chamberlin & Saper 1994, 1998Dutschmann & Herbert 1998, 2006Okazaki et al 2002). However, these pontinemediated responses were attributed to various protective reflex behaviours (Dutschmann et al 2004) and were not interpreted as a critical contribution of the pons to IOS and IE phase transition during normal breathing.…”
Section: General Pathways For Inspiratory/ Expiratory Phase Transitionsmentioning
confidence: 99%